2004
DOI: 10.1111/j.1349-7006.2004.tb02201.x
|View full text |Cite
|
Sign up to set email alerts
|

Methylenetetrahydrofolate reductase C677T and A1298C polymorphisms and colorectal cancer: The Fukuoka Colorectal Cancer Study

Abstract: Methylenetetrahydrofolate reductase (MTHFR) is a key enzyme regulating folate metabolism, which affects DNA synthesis and methylation. This study investigated the relation of MTHFR C677T and A1298C polymorphisms to colorectal cancer in a case-control study in Fukuoka, Japan. The subjects comprised 685 incident cases of histologically confirmed colorectal adenocarcinomas and 778 community controls selected randomly in the study area. The genotype was determined by the PCR-RFLP method using genomic DNA extracted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
89
6

Year Published

2005
2005
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(102 citation statements)
references
References 27 publications
(47 reference statements)
7
89
6
Order By: Relevance
“…However, the results are greatly inconsistent among various as well as within the same cancer sites. Some of these studies reported that MTHFR 677T allele carriers have reduced risks of colorectal [5][6][7][8][9], leukemia [10][11][12], and lung cancers [29]. In contrast, other studies reported elevated risks of esophageal [17], gastric [18], ovarian [30], cervical [14], bladder [13], colorectal [31,32], and lung cancers [33] for MTHFR 677T allele carriers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the results are greatly inconsistent among various as well as within the same cancer sites. Some of these studies reported that MTHFR 677T allele carriers have reduced risks of colorectal [5][6][7][8][9], leukemia [10][11][12], and lung cancers [29]. In contrast, other studies reported elevated risks of esophageal [17], gastric [18], ovarian [30], cervical [14], bladder [13], colorectal [31,32], and lung cancers [33] for MTHFR 677T allele carriers.…”
Section: Discussionmentioning
confidence: 99%
“…Genotypes with the MTHFR 677T allele have been related to protective effects on colon/rectum cancer [5][6][7][8][9], acute lymphocytic leukemia [10][11][12], and increased cancer risk of the bladder [13], cervix [14], breast [15,16], esophagus [17], and stomach [18]. However, only one epidemiological study estimated the relationship between MTHFR polymorphisms and liver cancer among patients with alcoholic cirrhosis and suggested that the MTHFR 677CC genotype increased the risk of developing HCC among patients with high alcohol consumption [19].…”
Section: Introductionmentioning
confidence: 99%
“…After discarding overlapping references and those which clearly did not meet the criteria, 22 studies were further assessed for eligibility (Park et al, 1999;Matsuo et al, 2002;Huang et al, 2003;Jiang et al, 2004;Kim et al, 2004;Yin et al, 2004;Jiang et al, 2005;Matsuo et al, 2005;Miao et al, 2005;Otani et al, 2005;Chang et al, 2007;Jin et al, 2007;Cao et al, 2008;Zhang et al, 2008;Cui et al, 2010;Promthet et al, 2010;Yang et al, 2010;Zhu et al, 2010;Kang et al, 2011;Kim et al, 2011;Zhu et al, 2011;Kim et al, 2012). After reviewing each original paper and extracting data, one study was excluded for overlapping data (Jiang et al, 2004).…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
“…As T allele dose increases, this functional polymorphism causes a graded elevation in tHcy in the mild-moderate range, most pronounced in individuals with low dietary folate consumption (Frosst et al, 1995). Thus, considering the potential influence on Zhen Yang*, Xie-Fu Zhang, Hong-Xiang Liu, Yong-Shun, Hao, Chun-Lin Zhao folate metabolism, many epidemiological studies have explored the association between the MTHFR C677T polymorphism and CRC risk, but the results are conflicting (Park et al, 1999;Matsuo et al, 2002;Kim et al, 2004;Yin et al, 2004;Otani et al, 2005;Chang et al, 2007;Cao et al, 2008;Cui et al, 2010;Promthet et al, 2010;Kim et al, 2011;Zhu et al, 2011). Small genetic association studies have various designs, different methodology and insufficient power, and could inevitably increase the risk that chance could be responsible for their conclusions, while combining data from all eligible studies by meta-analysis has the advantage of reducing random error and obtaining precise estimates for some potential genetic associations .…”
Section: Introductionmentioning
confidence: 99%
“…In fact, carriage of the 677T allele was associated with an elevated risk of developing esophageal (Song et al, 2001), gastric (Shen et al, 2001), ovarian (Gershoni-Baruch et al, 2000), and lung (Siemianowicz et al, 2003) cancer, and with a reduced risk in colorectal (Ma et al, 1997;Slattery et al, 1999;Yin et al, 2004) and lung (Jeng et al, 2003) cancer and in leukemia (Franco et al, 2001;Skibola et al, 1999).…”
Section: Discussionmentioning
confidence: 99%